Golden Era of Cataclysmic Variables and Related Objects II: Concluding Remarks - R. Hudec (Acta Polytechnica CTU Proceedings, 2015)
The cataclysmic variables continue to represent important part of modern astrophysics, as demonstrated, already second time, by the productive and successful conference Golden Era of Cataclysmic Variables and Related Objects II held on Mondello (Palermo) in September 2013.